World Economic and Financial Surveys : International Capital Markets, 1989. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper assesses recent trends in international capital markets. It reviews, in particular, the forces currently reshaping the markets of industrial countries and confronting financial institutions with major challenges. For the international capital markets, 1988 was generally a year of recovery. The international securities markets, depressed during the second and third quarters of 1987 and badly shaken by the October market break, rebounded in 1988. Intensifying competition and changing regulatory requirements characterize contemporary financial markets. Competition has been fostered by the internationalization of institutions, the liberalization of domestic markets, technological advances in data processing and telecommunications, and financial product innovations that more extensively link traditional banking and securities markets. A fundamental task of financial intermediaries is to appraise and assume risk and to charge for it appropriately. As a result of regulatory change, the growth of derivative product markets, and technological innovation, competitive pressure appears to be increasing the general level of risk assumed by intermediaries, while only partially providing the tools needed to manage that risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet